Trend in CV mortality among patients with mental disorder in the US between 1999–2020. (3rd October 2022) - Hamuda, N; Abert, T; Zahalka, M E; Zidan, A; Saada, M; Levi, Y; Abu Fanne, R; Meisel, S R; Roguin, A; Kobo, O
Abstract: Background: Patients with mental disorders are at increased risk of cardiovascular mortality. While the overall cardiovascular mortality rate in the western world is in decline, there is no up-to-date data on the cardiovascular mortality rates among patients with mental disorders. We aimed to assess the cardiovascular mortality trends over the last two decades among patients with mental co-morbidities in the US. Methods: Using Centers for Disease Control and Prevention Wide-Ranging, Online Data for Epidemiologic Research (CDC WONDER) Multiple Cause of Death data set, we determined national trends in age-standardized mortality rates attributed to cardiovascular diseases in patients with and without mental disorders, from 1999 to 2020, stratified by mental disorders subtype, age, gender, race, and place of residence. Results: Among more than 18.7 million cardiovascular deaths in the United States, 13.5% were patients with a concomitant mental disorder. During the study period, among patients with mental disorders, the age-adjusted mortality rate increased by 113.9% (vs 44.8% decline in patients with no mental disorder). In patients with mental disorders, the age-adjusted mortality rate increased more significantly among patients whose mental disorder in secondary to substance abuse (+532.6%) than among with organic mental disorders, such as dementia or delirium (+6.2%), while among patients with mood disorders the age-adjusted CV mortality rate dropped by 23.5%. Men patients, minorities, and residents of more rural areas experienced a more prominent increase in the age-adjusted cardiovascular mortality compared to women, white, and residents of metro areas. Conclusions: While there was an overall reduction in cardiovascular mortality in the US in the past two decades, we demonstrated an overall increase in cardiovascular mortality among patients with mental disorders. The increase was more significant among patients with substance abuse-related mental disorders, in men, minorities, and residents of rural areas. Funding Acknowledgement: Type of funding sources: None.